The ‘FebBenz’ approach for severe difficult-to-treat gout - Enrique Calvo-Aranda; Claudia María Gómez-González; Fernando Pérez-Ruiz; Marta Novella-Navarro (Exploration of Musculoskeletal Diseases)
Aim: To evaluate the efficacy and tolerability of febuxostat (FBX) and benzbromarone (BNZ) combination therapy in patients with difficult-to-treat (D2T) gout. Methods: This observational study was performed at two centers and included patients fulfilling the 2015 European Alliance of Associations for Rheumatology/American College of Rheumatology (EULAR/ACR) gout classification criteria, with clinical tophi and suboptimal response to standard urate-lowering therapy. A two-step treatment regimen was implemented: a 6-month dose escalation of the FBX dose followed by add-on BNZ. Demographic, clinical, and laboratory data—including cardiovascular risk factors (CVRFs), history of nephrolithiasis, liver enzymes, and estimated glomerular filtration rate (eGFR)—were recorded. Changes in serum urate (SUA) and eGFR were analyzed using paired t-tests. Results: The study population comprised 15 patients (87% male, median age 59 years) with longstanding gout [median 15 years, range 3–31; interquartile range (IQR) 8–25]. Baseline SUA was 10.3 ± 1.7 mg/dL; mean eGFR was 63.7 ± 23.6 mL/min. CVRFs were common (hypertension, 93%; dyslipidemia, 73%: major adverse cardiovascular events, 13%; diabetes, 7%). At 12 months, SUA had decreased significantly to 2.9 ± 1.1 mg/dL (Δ = 7.4 mg/dL; p < 0.01), with FBX alone contributing to a Δ of 5.4 mg/dL and BNZ an additional Δ of 2.1 mg/dL (both p < 0.01). Tophi resolved in 60% of patients. No serious adverse events or significant changes in liver or renal function were observed. One unrelated death was recorded. Conclusions: FBX + BNZ was effective and well-tolerated in patients with severe D2T gout, achieving a substantial reduction in SUA and clinically significant dissolution of tophi.